Expression of a splice variant of the platelet-activating factor receptor transcript 2 in various human cancer cell lines - Ibtissam Youlyouz; Emmanuelle Magnoux; Laurence Guglielmi; Yves Denizot (Mediators of Inflammation)
Platelet-activating factor receptor (PAF-R) transcripts were analysed by reverse transcriptase-polymerase chain reaction in five human cancer cell lines derived from the breast (BT20, SKBR3 and T47D cells), the pancreas (Miapaca cells) and the bladder (5637 cells) in order to confirm the existence of a splice variant of the PAF-R transcript 2. After cloning and sequencing, we confirmed its existence in all cell lines. It consisted of the PAF-R transcript 2 lengthening with 82 nucleotides from the 3' end of exon 1 of the PAF-R gene. The role of this elongated form of the tissue-type PAF-R transcript in cell physiology remains to be elucidated.